2020
DOI: 10.4148/1051-0834.2307
|View full text |Cite
|
Sign up to set email alerts
|

Impacting Agriculture and Natural Resource Policy: County Commissioners’ Decision-Making Behaviors and Communication Preferences

Abstract: Elected officials at the local, state, and national levels play key roles in shaping the agriculture and natural resources (ANR) sectors through the development and implementation of ANR policies and regulations. As such, it has become necessary for members of the ANR community to understand the policy formation process and how to communicate effectively with elected officials about ANR policies and issues. However, little research has been conducted at the local level to examine how local elected officials (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…They reported higher perceived impact of such communication at the local level of government than with state or national legislators, which may explain why a larger number of respondents had previously contacted a local official than one at the state and national levels. In a prior study conducted with county commissioners, Lawson et al (2020) found county commissioners were most impacted by communication from a farmer or rancher when making ANR policy decisions. Such information should be shared with AO members who have not sought to engage in ANR policy and/or are less convinced of the impact of their communication on influencing policy decisions.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported higher perceived impact of such communication at the local level of government than with state or national legislators, which may explain why a larger number of respondents had previously contacted a local official than one at the state and national levels. In a prior study conducted with county commissioners, Lawson et al (2020) found county commissioners were most impacted by communication from a farmer or rancher when making ANR policy decisions. Such information should be shared with AO members who have not sought to engage in ANR policy and/or are less convinced of the impact of their communication on influencing policy decisions.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…Agriculture organization (AO) members are key stakeholders within the ANR sector, and their engagement and participation in policy decisions can have a significant impact on policy formulation and implementation (Reimer, 2013). For example, in a prior study conducted by Lawson et al (2020) county commissioners identified communication from a farmer or rancher as the factor that would most influence their decision-making when voting on an ANR policy. While policy engagement among agricultural advocacy groups is not a new concept, the frequency of engagement among agricultural groups has remained slightly less than other key policy areas, such as environmental and healthcare policy (Grossman, 2012).…”
Section: Introductionmentioning
confidence: 99%